Madrasah Ibtidaiyah Satisfaction Towards The Performance Of Their Supervisors - A.M. Wibowo; Dwi Istiyani (FITK UIN Walisongo, 2022)
This article aimed to measure the satisfaction of Madrasah Ibtidaiyah toward the performance of their supervisors in Kebumen Regency, IndonesiaThis research is important because the performance of madrasa supervisors is thought to affect the quality of education in Madrasas, both managerial and academic. The object of the research was conducted at the madrasah ibtidaiyah education unit with a locus in Kebumen Regency, Central Java. The Madrasah ibtidaiyah satisfaction toward the performance of supervisors was measured based on the expectations and reality of responsiveness, reliability, empathy, assurance, and tangibles of supervisors to madrasah ibtidaiyah. Through the analysis of the Customer Satisfaction Index (CSI), this study found out two conclusions. First, there was an unbalanced ratio of the number of supervisors to the number of Madrasah Ibtidaiyah. Second, although the unbalanced ratio number of supervisors and Madrasah Ibtidaiyah, Madrasah Ibtidaiyah were satisfied toward the supervisory performed by their supervisors, both managerial and academic.